Manajemen Krisis Direktorat Jenderal Bea dan Cukai Kementerian Keuangan dalam Mengembalikan Kepercayaan Publik - Ramdani, Adisti Citra; Budiana, Heru Ryanto; Prastowo, FX Ari Agung (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
A crisis hit the Directorate General of Customs and Excise (DJBC) in April 2024, triggered by the widespread virality of issues related to delivered goods on social media. These viral issues included Radhika Althaf's shoe issue, Ijal Zaid's SLB aid issue, and Medy Renaldy's toy issue. This study aims to examine how DJBC's crisis management efforts worked to restore public trust. The research uses a qualitative method with a case study approach. The findings indicate that DJBC's crisis management is divided into three main stages: pre-crisis, including preparation, prevention, and issue detection and identification; crisis, which involves issue assessment, data collection, determination of crisis communication strategies, and execution of crisis communication; and post-crisis, which includes monitoring and evaluation, continued communication, and learning from the crisis. This study shows that DJBC's crisis management SOP aligns with crisis management concepts proposed by experts. Crisis communication efforts during the crisis included a personal approach, initial social media handling, crisis response content, media briefings, the use of KBPJ spokespersons, bolstering, and the use of a primary spokesperson.